The Three Hundred project: Radio luminosity evolution from merger-induced shock fronts in simulated galaxy clusters - Nuza, Sebastian Ernesto (2024)
Context. Galaxy cluster mergers are believed to generate large-scale shock waves that are ideal sites for cosmic ray production. In these so-called radio relic shocks, synchrotron radiation is produced mainly as a result of electron acceleration in the presence of intracluster magnetic fields. Aims. We aim to compute radio emission light curves for a sample of galaxy group and cluster mergers simulated in a cosmological context in order to study the dependence of radio luminosity on cluster mass, redshift, and impact parameter. Methods. We used model galaxy clusters from THE THREE HUNDRED project, a sample of 324 simulated high-density regions of radius 15 h −1 Mpc extracted from a cosmological volume, to identify cluster mergers characterised by the two main merging structures, construct their light curves, and follow their evolution throughout the complete simulated cosmic history. Results. We found that the median non-thermal radio relic luminosity light curve produced in galaxy cluster mergers can be described by a skewed Gaussian function abruptly rising after core-passage of the secondary cluster that peaks after ∼0.1–0.8 Gyr as a function of M200,1, the mass of the primary, displaying a mass-dependent luminosity output increase of ≲10 to about ≳10–50 times relative to the radio emission measured at core-passage for galaxy groups and clusters, respectively. In general, most merger orbits are fairly radial with a median opening angle of ∼20◦ before the collision. We also found that, independent of the cluster mass, less radial mergers tend to last longer, although the trend is weak. Finally, in agreement with previous works, we found that the peak radio luminosity shows a significant correlation with mass, P1.4 ∝ M2.05 200,1 , demonstrating that this relation holds all the way up from galaxy group scales to the most massive galaxy clusters. Conclusions. We conclude that cluster mass is the primary driver for radio ‘gischt’ median luminosity, although there are significant variations for a given cluster mass related to the specifics of each merging process. In general, binary mergers are responsible for many of the well-known observed radio relic structures but complex situations involving three or more substructures are also common. Our simulations suggest that the shock-driven, non-thermal radio emission observed on cluster outskirts are the result of massive galaxy cluster mergers at z ≲ 1, peaking at z ∼ 0–0.5.